TGF-β1/SH2B3 axis regulates anoikis resistance and EMT of lung cancer cells by modulating JAK2/STAT3 and SHP2/Grb2 signaling pathways - Wang, Li-Na; Zhang, Zi-Teng; Wang, Li; Wei, Hai-Xiang; Zhang, Tao; Zhang, Li-Ming; Lin, Hang; Zhang, Heng; Wang, Shao-Qiang (Cell death & disease, 2022)
The pathogenesis of lung cancer, the most common cancer, is complex and unclear, leading to limited treatment options and poor prognosis. To provide molecular insights into lung cancer development, we investigated the function and underlying mechanism of SH2B3 in the regulation of lung cancer. We indicated SH2B3 was diminished while TGF-β1 was elevated in lung cancer tissues and cells. Low SH2B3 level was correlated with poor prognosis of lung cancer patients. SH2B3 overexpression suppressed cancer cell anoikis resistance, proliferation, migration, invasion, and EMT, while TGF-β1 promoted those processes via reducing SH2B3. SH2B3 bound to JAK2 and SHP2 to repress JAK2/STAT3 and SHP2/Grb2/PI3K/AKT signaling pathways, respectively, resulting in reduced cancer cell anoikis resistance, proliferation, migration, invasion, and EMT. Overexpression of SH2B3 suppressed lung cancer growth and metastasis in vivo. In conclusion, SH2B3 restrained the development of anoikis resistance and EMT of lung cancer cells via suppressing JAK2/STAT3 and SHP2/Grb2/PI3K/AKT signaling cascades, leading to decreased cancer cell proliferation, migration, and invasion.